Delay Aware Joint Routing and Scheduling for Multi-Tx-Rx Wireless Mesh Networks - Wang, L.; Chin, K.; Raad, R.; Soh, Sie Teng (IEEE, 2014)
Recently, researchers have created Wireless Mesh Networks (WMNs) where routers have multiple transmit (Tx) or receive (Rx) capability. A fundamental problem in such WMNs is deriving a transmission schedule that yields minimal end-to-end delays. In this paper, we approach this problem via joint routing and link scheduling. Specifically, we consider twofundamental issues that influence end-to-end delays: super frame length and transmission slot order. We propose two algorithms: JRS-Multi-DEC and JRS-BIP, where the former uses a novel metric to minimize the load of each link whilst the latter uses a binary integer program solver. Both algorithms have the similar aim of minimizing overall delay and to re-order slots such that packets are forwarded quickly along their path. Numerical results show that our algorithms can reduce average delay by approximately 50% as compared to a non joint routing and scheduling algorithm.